Analisis Laporan Profitabilitas Dan Resiko Keuangan PT. Riau Graindo Pekanbaru - Budi Dharma; Mustafaruddin Mustafaruddin; Idham Mahrivi (Jurnal Manajemen Akuntansi (JUMSI), 2023)
In this research, the object is the financial statements at PT. Riau Graindo Pekanbaru. The data drawn is based on the descriptive method, namely analyzing in the form of balance sheets and profit and loss reports, then connecting them with actual conditions and also connecting with supporting theories and carrying out internal comparisons by comparing financial ratios in each period. The form of data used by the author is secondary data, namely in the form of financial reports of PT. Riau Graindo Pekanbaru in the form of balance sheets and income statements from the period 2006,2007,2008,2009,2010. Other secondary data is in the form of company history, company profile and company organizational structure. The data collection technique used by the author is by conducting interviews, documentation, literature studies, and observation. This study aims to determine what factors cause fluctuations in the ratio of liquidity, solvency, profitability, activity at PT. Riau Graindo Pekanbaru.